2019
DOI: 10.1038/s41467-019-12231-4
|View full text |Cite
|
Sign up to set email alerts
|

Floquet Chern insulators of light

Abstract: Achieving topologically-protected robust transport in optical systems has recently been of great interest. Most studied topological photonic structures can be understood by solving the eigenvalue problem of Maxwell’s equations for static linear systems. Here, we extend topological phases into dynamically driven systems and achieve a Floquet Chern insulator of light in nonlinear photonic crystals (PhCs). Specifically, we start by presenting the Floquet eigenvalue problem in driven two-dimensional PhCs. We then … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…By mapping the tensors (24)(25)(26) to the set of effective bianisotropic parameters in Eqs. (19)(20)(21)(22), we determine,…”
Section: Equivalent Moving Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…By mapping the tensors (24)(25)(26) to the set of effective bianisotropic parameters in Eqs. (19)(20)(21)(22), we determine,…”
Section: Equivalent Moving Mediummentioning
confidence: 99%
“…Modulation of the electric permittivity in space and time has attracted much attention, as it gives rise to a plethora of exotic effects ranging from frequencymomentum transitions [6,7] to compression and amplification of electromagnetic signals [8][9][10][11][12][13][14] and even non-Hermitian and topological phenomena [15][16][17][18][19]. The directionality of space-time modulations such as travellingwave modulations breaks time-reversal symmetry, which is reflected in non-reciprocal band diagrams [4].…”
Section: Introductionmentioning
confidence: 99%
“…We show how the concept of "luminal grating" can yield giant nonreciprocity, achieve efficient one-way amplification, pulse compression and frequency up-conversion, proposing a realistic implementation in double-layer graphene.Temporal control of light is a long-standing dream, which has recently demonstrated its potential to revolutionize optical and microwave technology, as well as our understanding of electromagnetic theory, overcoming the stringent constraint of energy conservation [1]. Along with the ability of time-dependent systems to violate electromagnetic reciprocity [2][3][4], realising photonic isolators and circulators [5][6][7][8], amplify signals [9], perform harmonic generation [10,11] and phase modulation [12], new concepts from topological [13][14][15] and non-Hermitian physics [16,17] are steadily permeating this field.However, current limitations to the possibility of significantly fast modulation in optics has constrained the concept of time-dependent electromagnetics to the radio frequency domain, where varactors can be used to modulate capacitance [18], and traveling-wave tubes are commonly used as (bulky) microwave amplifiers [19]. In the visible and near IR, optical nonlinearities have often been exploited to generate harmonics, and realize certain nonreciprocal effects [20].…”
mentioning
confidence: 99%
“…Temporal control of light is a long-standing dream, which has recently demonstrated its potential to revolutionize optical and microwave technology, as well as our understanding of electromagnetic theory, overcoming the stringent constraint of energy conservation [1]. Along with the ability of time-dependent systems to violate electromagnetic reciprocity [2][3][4], realising photonic isolators and circulators [5][6][7][8], amplify signals [9], perform harmonic generation [10,11] and phase modulation [12], new concepts from topological [13][14][15] and non-Hermitian physics [16,17] are steadily permeating this field.…”
mentioning
confidence: 99%
“…The superchiral field can also enhance the difference between total optical forces on enantiomers, which promises the development of application for chiral molecule sorting. Recent investigation has shown that superchiral field has a potential application on the enantioselective conversion in reactions [14], extending its use from the all-optical areas to photochemistry fields. Because of its high importance in all these applications, the superchiral field has bloomed in the last 10 years, and intense theoretical and experimental studies have been devoted to the generalization of strong superchiral nearfields with the help of artificial nanostructures [15][16][17][18][19][20][21][22][23][24][25].…”
mentioning
confidence: 99%